PENGARUH RISIKO LITIGASI TERHADAP MANAJEMEN LABA DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERATING - Atiqah, Miratul; Purwanto, Agus (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2011)
Asymmetry of information between agency and principal, make the management have opportunityto create earnings management. Earnings management has a disadvantage to investors. Auditorshave a risk that investor can make a assertion to auditor is called litigation risk. The purposeof this research is to examine the influence of Litigation Risk to Earnings Management and theinfluence Audit Quality as the moderating variable in relations between Litigation Risk andEarnings Management. The proxy for earnings management is discretionary accruals by JonesModel (performance-matched discretionary accruals). Audit Quality in this research use auditorsize. This study uses secondary data from financial statement of manufacturing companies whichlisted on Bursa Efek Indonesia in 2008-2010. This research uses purposive sampling method. Themethod analysis of this research used multiple regression analysis.The results of this research show that litigation risk had no influence on earnings management.The result of the test to moderating variable shows that audit quality had negative influence onthe relations between Litigation Risk and Earnings Management.